«Избранные стихотворения» Софии Дубновой-Эрлих в архиве М. Волошина [“Selected Poems” by Sofia Dubnova-Erlich in Maximilian Voloshin’s Archive] - Lavrov, Alexander (Slavica Revalensia, 2026)
The article introduces the poetry collection of a lesser-known Russian poet from the beginning of the 20th century, Sofia Dubnova-Erlich, the publication of which is based on the holograph draft discovered in the archive of Maximilian Voloshin. The collection of poems reached Voloshin through Mikhail Vinaver, who was one of the founders of the Moscow Political Red Cross. This organisation, headed by Ekaterina Peshkova, helped political prisoners in Soviet Russia. The article also provides a brief overview of Dubnova’s social activities, as well as her poetic output, in which she saw a chance to combine her Russian and Jewish identities organically.